2016
DOI: 10.1002/hbm.23157
|View full text |Cite
|
Sign up to set email alerts
|

Test-retest reliability of the default mode network in a multi-centric fMRI study of healthy elderly: Effects of data-driven physiological noise correction techniques

Abstract: Understanding how to reduce the influence of physiological noise in resting state fMRI data is important for the interpretation of functional brain connectivity. Limited data is currently available to assess the performance of physiological noise correction techniques, in particular when evaluating longitudinal changes in the default mode network (DMN) of healthy elderly participants. In this 3T harmonized multisite fMRI study, we investigated how different retrospective physiological noise correction (rPNC) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 62 publications
1
31
0
Order By: Relevance
“…Researchers continue to take seriously the effort to systematically measure the factors that influence test/retest reliability of responses across time and tasks, and these sorts of studies are increasingly common. [83][84][85][86][87][88] Other research programs focus on addressing questions about the long-term within-subject stability of responses 89,90 and how the accurate assessment of within-participant differences might address questions about individual differences. [91][92][93] There is increasing support for conducting and publishing the results of confirmatory studies, 94,95 thereby rectifying some existing biases that often favor the publication of new, novel results over confirmatory ones.…”
Section: Results Reproducibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers continue to take seriously the effort to systematically measure the factors that influence test/retest reliability of responses across time and tasks, and these sorts of studies are increasingly common. [83][84][85][86][87][88] Other research programs focus on addressing questions about the long-term within-subject stability of responses 89,90 and how the accurate assessment of within-participant differences might address questions about individual differences. [91][92][93] There is increasing support for conducting and publishing the results of confirmatory studies, 94,95 thereby rectifying some existing biases that often favor the publication of new, novel results over confirmatory ones.…”
Section: Results Reproducibilitymentioning
confidence: 99%
“…Despite the acknowledged lack of consensus about how to measure and thereby evaluate results reproducibility and the noted significant problems with statistical power, we find a number of encouraging developments concerning the reproducibility of results. Researchers continue to take seriously the effort to systematically measure the factors that influence test/retest reliability of responses across time and tasks, and these sorts of studies are increasingly common . Other research programs focus on addressing questions about the long‐term within‐subject stability of responses and how the accurate assessment of within‐participant differences might address questions about individual differences .…”
Section: Recent Initiativesmentioning
confidence: 99%
“…Researchers continue to take seriously the effort to systematically measure the factors that influence test/ retest reliability of responses across time and tasks, and these sorts of studies are increasingly common [83][84][85][86][87][88] . Other research programs focus on addressing questions about the long-term within-subject stability of responses [89][90] , and how the accurate assessment of within-participant differences might address questions about individual differences 93 .…”
Section: Results Reproducibilitymentioning
confidence: 99%
“…These artifacts are often dealt with in addition to motion, either by modeling a movement‐related phase‐shift in each EPI acquisition, combined with a canonical hemodynamic response function to respiration and heart rate [Birn et al, ; Chang et al, ]; by using a proxy correction by assuming that the BOLD signal fluctuations in the deep WM and CSF encode non‐neuronal variations in respiration and heart rate signals [Birn, ]; or by using dual‐echo acquisition methods that can help separate true noise from biologically relevant signals [Bright and Murphy, ]. To date, the majority of work examining the impact of physiological correction on resting‐state fMRI has focused on improved consistency of the DMN [Marchitelli et al, ], although in some cases, the DMN and the respiration component identified from ICA may be overlapping [Birn et al, ]. In fact, it has been shown that respiration‐related changes in end‐tidal CO 2 create anatomically specific patterns in many temporal (e.g., Insula) and medial brain areas (e.g., cingulate cortex) that are commonly studied in pharmacological studies [Peng et al, ; Wise et al, ].…”
Section: Challenges and Limitationsmentioning
confidence: 99%